Experimental Modeling of Wind Resources for Electricity Generation in the Ningo‐Prampram Region of Ghana - Johannes Ami; Ato Fanyin‐Martin; John Stephen Asamoah; Nana Yaw Asiedu; Bright Amponsem; Matthew Kwofie (Energy Science & Engineering)
ABSTRACT Wind energy, as a renewable energy source, plays a critical role in achieving the world's energy transition goals. This study assesses the wind resource characteristics and potential for wind power production in the Ningo‐Prampram District of Ghana. On‐site wind measurements were conducted using an air flow anemometer at various reference points within the study area. The collected site data were statistically validated against existing satellite data using T‐test analysis, which revealed no significant difference between the ground and satellite measurements (p > 0.05), despite observed changes in weather patterns. The results showed that the mean wind speed in the area ranged between 4 and 5.6 m/s at a height of 10 m, with a predominant wind direction from the East. The district exhibited a moderate turbulence intensity of 0.226, indicating fairly good suitability for wind power projects. A feasibility analysis determined that the study area, covering 142.03 km², has the potential to accommodate a 40 MW wind farm using 20 Enercon‐82‐E2 wind turbines (2 MW each) with an 80 m hub height. This installation could reduce Ghana's Wind Utility Scale total target for 2030 by 25.256%. These findings suggest that the Ningo‐Prampram District possesses favorable conditions for sustainable wind power development.